Beryllium-10 measurements from Cumberland Peninsula, Baffin Island and Kangiata Nunaata Sermia outlet glacier, Southwestern Greenland, 2015-2019 - Young, Nicolas; Schaefer, Joerg; Briner, Jason; Miller, Gifford (Arctic Data Center, 2019)
Beryllium-10 measurements from two alpine valleys on the Cumberland Peninsula, Baffin Island and the Kangiata Nunaata Sermia forefield, southwestern Greenland. Be-10 ages constrain the timing of deglaciation at each site. All of necessary input parameters are provided to independently calculate Be-10 ages.